Disseminated intravascular coagulation associated organ failure in obstetric patients admitted to intensive care units: a multicenter study in China - Zhiling Zhao; Jianxin Zhang; Nan Li; Gaiqi Yao; Yangyu Zhao; Shuangling Li; Qinggang Ge; Junli Lu; Shining Bo; Jingjing Xi; Yue Han (Scientific Reports, 2021)
Abstract We aimed to determine disseminated intravascular coagulation (DIC)-associated organ failure and underlying diseases based on data from three ICU wards in tertiary hospitals in China from 2008 to 2016. The diagnosis of DIC was confirmed by an International Society of Thrombosis and Hemostasis score greater than or equal to 5. The maternal outcomes included the changes in organ function 24 h after ICU admission. The durations of hospital stay and ICU stay were recorded as secondary outcomes. Among 297 ICU admissions (median Sequential Organ Failure Assessment score, 4) for obstetric diseases, there were 87 DIC cases, with an estimated DIC incidence of 87 per 87,580 deliveries. Postpartum hemorrhage was the leading disease associated with DIC (71, 81.6%), followed by hypertensive disorders (27, 31.0%), sepsis (15, 17.2%), acute fatty liver of pregnancy (11, 12.6%) and amniotic fluid embolism (10, 11.5%). Compared with patients without DIC, those with DIC had higher rates of multiple organ dysfunction syndrome/death (27.6% vs 4.8%, p = 0.000), organ failure (36.8% vs 24.3%, p = 0.029), among which organ failure included acute renal failure (32.2% vs 10.0%, p = 0.000), respiratory failure (16.1% vs 8.6%, p = 0.057), disturbance of consciousness (12.6% vs 2.4%, p = 0.000) and DIC group also had higher rates of massive transfusion (52.9% vs 21.9%, p = 0.000), hysterectomy (32.2% vs 15.7%, p = 0.001), longer ICU (4 days vs 2 days, p = 0.000) and hospital stays (14 days vs 11 days, p = 0.005). DIC and amniotic fluid embolism were independent risk factors for organ failure in patients admitted to the ICU. Postpartum hemorrhage was the leading cause of DIC associated organ failure in obstetrics admitted to the ICU. The control of obstetric bleeding in a timely manner may improve obstetric prognoses.